Library Management Strategy to Strengthen Literacy Culture in Elementary Schools - Mastur Mastur (Jurnal Basicedu, 2023)
This study seeks to determine the strategy of library management as a means of literacy culture in elementary schools. This study aimed to determine the involvement of school libraries and librarians in enhancing literacy culture in elementary schools. This study uses a qualitative method with a case study approach. Data collection techniques using in-depth interviews, observation, and documentation. Informants in this study were school librarians at MIN 1 Tulungagung. Data analysis techniques include data collection, reduction, presentation, and conclusion. The study results show that the role of the school library in implementing literacy culture includes preparing facilities and infrastructure, facilitating school literacy movement activities, as a facilitator and preparing all the needs for the continuation of the school literacy movement.